Is the Frequency of Smoking Affecting the Risk of Abusing Cannabis? - Astuti, Nurul Huriah; Hastono, Sutanto Priyo (KEMAS: Jurnal Kesehatan Masyarakat, 2020)
The results of previous study found that teens that had a smoking habit were 14 times more likely to smoke cannabis than those who did not smoke. This study aims to determine the relationship between the frequency of smoking and cannabis abuse done through survival analysis. The research samples were 708 students of cannabis abusers who were previously preceded by smoking. The results of this study found that durability or length of time for abusing cannabis was mostly 1 – 4 years. The Wilcoxon test results concluded that there was a difference in survival to abusing cannabis among the frequency groups of smoking. Multivariate analysis also showed that the more number of cigarettes consumed, the greater the risk for abusing cannabis after being controlled by confounders. Conclusion of this study, the frequency of smoking affects the survival rate and the amount of risk to abusing cannabis.